On modelling heat and moisture transfer in sandwich wall and slab structures - Nikitin, Vadim; Lapko, Andrzej (Journal of Civil Engineering and Management, 2006)
In real wall or slab structures made of capillary‐porous materials (such as masonry or concrete) exposed to ambient air, the unsteady processes of heat transfer and moisture migration as reciprocal phenomena are observed. Basing on the Fourier general differential equations and using the assumptions of the elementary heat balance method, the problem of heat and moisture transfer has been studied in multi‐layer wall structures, such as sandwich panels. As a result the general equations were proposed and transformed into formulas useful in the FDM approach (Finite Difference Method). On this basis a computer program was written to analyse the phenomena mentioned above. Some computational tests for a concrete sandwich panel wall with insulation made of foamed polyurethane were presented and discussed to illustrate a possible application of this approach. The paper shows that the improvement of computational accuracy of modelling the thermal engineering problems requires an assumption of real parameters which characterise capillary‐porous structural materials and result from moisture transfer.Apie šilumos ir drėgmės sklidimo sluoksniuotųjų sienų ir plokščių konstrukcijose modeliavimąSantrauka. Daugelio pastatų sienų ir plokščių konstrukcijos pagamintos iš porėtų medžiagų (tokių kaip mūras ar betonas). Šios konstrukcijos yra veikiamos aplinkos poveikių, dėl to jose vyksta nestacionarūs šilumos bei drėgmės sklidimo procesai. Šilumos ir drėgmės sklidimo daugiasluoksnėse konstrukcijose problema nagrinėta remiantis bendrosiomis Furjė diferencialinėmis lygtimis bei šilumos balanso metodo prielaidomis. Pasiūlytos bendrosios išraiškos, kurios transformuotos į formules, taikomas baigtinių skirtumų metodui. Šiai problemai analizuoti sukurta kompiuterinė programa ir algoritmas, pritaikytas sluoksniuotajai betoninei plokštei su poliuretano izoliacija.Reikšminiai žodžiai: šilumos perdavimas, drėgmės sklidimas, sluoksniuotosios sienos, skaitiniai metodai, analizė, ilgaamžiškumas.First Published Online: 14 Oct 2010